Diagnostic accuracy of diaphragm ultrasound to predict weaning outcome: A systematic review and meta-analysis. (May 2021) - Le Neindre, Aymeric; Philippart, François; Luperto, Marta; Wormser, Johan; Morel-Sapene, Johanna; Aho, Serge L.; Mongodi, Silvia; Mojoli, Francesco; Bouhemad, Belaid
Abstract: Background: The accuracy of diaphragm ultrasound for predicting weaning outcome is still debated, despite the publication of numerous studies evaluating this issue. Objective: The aim of this systematic review and meta-analysis was to assess the diagnostic accuracy of diaphragm ultrasound for predicting weaning failure in critically ill patients. Design and data sources: MEDLINE, Science direct, Cochrane Library, EMBASE and CENTRAL were searched. Two investigators independently selected studies that met the inclusion criteria, and three extracted data and performed a bias analysis using the Quality Assessment of Diagnostic Accuracy Studies-2 instrument. A bivariate model was used to estimate the pooled results for sensitivity, specificity and diagnostic odds ratio. Sources of heterogeneity were explored, and subgroup analyses were performed. Results: Twenty-eight studies were included in the systematic review, from which 16 studies (816 patients in total) were included in the meta-analysis. The pooled sensitivity, specificity and area under the summary receiver operator characteristic curve were 0.70 (95% CI 0.57–0.80), 0.84 (95% CI 0.73–0.91), and 0.82 (95% Cl 0.78–0.85) for diaphragm thickening fraction, respectively, and 0.71 (95% CI 0.61–0.79), 0.80 (95% CI 0.73–0.86), and 0.82 (95% Cl 0.79–0.86) for diaphragm excursion, respectively. There was substantial heterogeneity among the studies. Meta-regression highlighted significant effects of prevalence of extubation failure, cut-off and risk of bias in flow and timing of the study on diaphragm ultrasound accuracy. By excluding outlier and influential studies, sensitivity was lower and specificity higher for diaphragm thickening fraction. Conclusion: The specificity of diaphragm ultrasound for predicting the risk of extubation failure in critically ill patients was moderate-to-high. However, sensitivity was low because weaning is also affected by non-diaphragm-related factors. Further research in subgroups of critically ill patients applying a homogeneous definition of weaning and uniformly conducted measure is needed to assess the accuracy of diaphragm ultrasound. Clinical Trial Registration: Registered on http://www.crd.york.ac.uk/PROSPERO as CRD42017058028. Tweetable abstract: Diaphragm ultrasound predicts extubation failure with high specificity. Absence of diaphragm dysfunction does not imply no risk of extubation failure.